N-Acetyl-Seryl-Aspartyl-Lysyl-Proline Mitigates Experimental Colitis Through Inhibition of Intestinal Mucosal Inflammatory Responses via MEK-ERK Signaling - Shi, Yingying; Zhou, Mingxia; Yan, Junkai; Gong, Zizhen; Wu, Jin; Chen, Yuanwen; Chen, Yingwei (Frontiers in Pharmacology, 2020)
N-acetyl-seryl-aspartyl-lysyl-proline (AcSDKP) is an endogenous immunomodulatory peptide that is generated from thymosin β4 (Tβ4) through stepwise hydrolysis involving meprin-α and prolyl endopeptidase (PREP). It’s well acknowledged that AcSDKP exerts beneficial effects on multiple cardiovascular and renal diseases. However, the functional role of AcSDKP in inflammatory bowel disease (IBD) remains poorly understood. Here, we aimed to estimate the generation rate of AcSDKP in human patients with IBD and investigate the impact of AcSDKP on intestinal inflammation in IBD. We found that in the inflamed mucosal specimens of patients with ulcerative colitis, expression levels of Tβ4 and meprin-α were decreased, while PREP was expressed at similar levels to non-inflamed mucosa. In vitro, AcSDKP was showed to inhibit the expression of proinflammatory factors in intestinal epithelial cells partially by reducing the activation of MEK-ERK signaling. In vivo, we demonstrated that transgenic mice with lower levels of AcSDKP were more vulnerable to DSS-induced colitis and exhibited more severe intestinal inflammatory responses, whereas exogenous AcSDKP infusion significantly attenuated the clinical symptoms and intestinal mucosal inflammation in DSS-induced mice. In conclusion, our data identify the anti-inflammatory function of AcSDKP within the intestine and suggest that AcSDKP has a promising therapeutic potential for IBD treatment.